Beliefs about Conjugal Violence: An Explanation from Human Values - Lopes, Bruna de Jesus (2022)
Objective. The present work aimed to discover the relationship between human values and beliefs about marital violence. Method. The sample was composed by 202 subjects from the general population of the city of Parnaíba-PI. The average age was 28.52 years (SD = 10.33). They were administered the following instruments: Belief on Marital Violence Scale (BMVS), Basic Values ​​Questionnaire (BVQ-18), and a Socio-demographic Questionnaire. The SPSS software (version 22) assisted in the execution of descriptive analysis, Pearson's correlation (r), and regression (Stepwise Methods). Results. The results showed that the Interactive, Suprapersonal, and Existence subfunctions present significant and inverse correlations with all dimensions of BMVS; they ratify the ability of human values to explain social constructs such as marital violence.